Chitosan as an antimicrobial agent for footwear leather components - Barros, M.C. (2010)
In the footwear industry, microorganisms’ growth can pose problems of material deterioration with associated unpleasant smell and generate possible infections in susceptible individuals. Generally, footwear presents high relative humidity conditions that enable the growth of bacteria and fungi. Additionally, leather itself and some tannery agents such as oils and greases, provide a substrate where microorganisms can grow. In the foot, microtraumas caused by ingrown nails, abrasions and lacerations can allow microbial invasion through epidermis, resulting in skin infection. In this work, the applicability of chitosan functional coatings to leather was tested, with the purpose to develop new base materials to produce footwear components. The leather treated with chitosan was then studied for its antibacterial properties against 3 different bacteria.